Faculty perceptions of critical thinking at a health sciences university - Joie Rowles; Christine Michelle Morgan; Shari Burns; Christine Merchant (Journal of the Scholarship of Teaching and Learning, 2013)
The fostering of critical thinking skills has become an expectation of faculty, especially those teaching in the health sciences. The manner in which critical thinking is defined by faculty impacts how they will address the challenge to promote critical thinking among their students. This study reports the perceptions of critical thinking held by health sciences faculty representing multiple disciplines. The results provide a working definition of critical thinking and its components, and indicate the importance that critical thinking is given in the education of health care students. Implications of these results for teaching and learning are presented.